Grassroots to global : broader impacts of civic ecology - Krasny, Marianne E. (Comstock Publishing Associates, an imprint of Cornell University Press, 2018)
"This edited volume presents diverse case studies about the implications of civic ecology practices worldwide. It answers how civic ecology practices emerge, the role the practices play in the ability of communities and individuals to address social-ecological stresses, and given climate-associated disturbances, what strategies can be used to expand impacts of community driven practices to foster large-scale resilience and sustainability"--